The provision of promotive and preventative healthcare services by private primary care physicians in the era of the national health insurance program - Ketut Ary Diana Artha; I Ketut Suarjana; Pande Putu Januraga (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: In addition to their duties in addressing the curative and rehabilitative needs of the community, private primary care physicians (PCP) play an important role in providing promotive and preventative healthcare services. This study aims to determine the behaviours, enabling and inhibiting factors involved with the provision of promotive and preventative services by PCP in the era of national health insurance (JKN) implementation. Methods: This research is a mix method study using a combination of quantitative and qualitative approaches. Quantitative surveys were conducted with all PCPs already in working collaboration with the Social Security Administering Agency (BPJS) in the Denpasar City area (61 people). Data analysis techniques used descriptive techniques in order to explore the kinds of promotion and preventative services provided by PCPs. Qualitative research was conducted through in-depth interviews of 8 informants selected by purposive sampling and analyzed thematically to discover the enabling and inhibiting factors of the provision of promotive and preventative services by PCPs. Results: The results showed that 91.8% of PCPs did perform promotive and preventative services in their practice site. PCPs who did not carry out promotive and preventative services demonstrate perceptions, beliefs and motivations categorized as low and weak as well as attitudes that do not support the implementation of such services. Enabling factors of promotion and preventative services by PCPs, include among others, quality of facilities and infrastructure, the receipt of awards from BPJS and capitation systems that benefit physicians financially. Inhibiting factors include a low willingness of the patient to carry out doctor's advice, limitations in the PCPs work time and limited funds to perform preventative/promotive services. Conclusions: Promotive and preventative services are not being optimally carried out by PCPs in Denpasar. This is due to the low willingness of the patients, the limited time of the doctor, and the limited allocated funds for promotive and preventative services and low capitation.